Chiral separation of d/l-arginine with whole cells through an engineered FhuA nanochannel. Issue 38 (27th March 2019) - Anand, Deepak; Dhoke, Gaurao V.; Gehrmann, Julia; Garakani, Tayebeh M.; Davari, Mehdi D.; Bocola, Marco; Zhu, Leilei; Schwaneberg, Ulrich
Abstract : Development of a novel whole cell system for chiral separation of arginine enantiomers through an engineered outer membrane channel protein ferric hydroxamate uptake protein A (FhuA). Abstract : Downstream processing to obtain enantiopure compounds from a racemic mixture relies mainly on crystallization. Natural transporters can specifically translocate enantiomers through membranes. Here a β-barrel transmembrane protein FhuA is re-engineered into a chiral channel protein (FhuAF4) to resolve racemic mixtures ofd -/l -arginine. The engineered FhuAF4 variant exhibits an enantioselectivity ( E -value) of 1.92 and an enantiomeric excess percentage (ee%) of 23.91 at 52.39% conversion. OmniChange mutant libraries at the computationally identified "filter-regions" likely help to identify FhuA variants for enantiomeric separation of other compounds.